Analysis of Segmentation, Targeting, and Positioning (STP) Determination on Sales Volume at Cafe Teras Empang Parepare City - Ilham Abu; Ridwan Ridwan (Fundamental and Applied Management Journal, 2023)
This study aims to assess and analyze whether the STP (Segmentation, Targeting, and Positioning) marketing strategy on the sales volume that has been implemented by Cafe Teras Empang in Parepare City has reached approximately one year (2021-2022). This type of research is descriptive quantitative. The population in this study were all employees of Cafe Teras Empang while the sample of this study were all 36 employees of Cafe Teras Empang as respondents using saturated sampling, which is a sampling technique when all members of the population are used as samples. The data collection techniques were carried out by means of questionnaires conducting interviews and questionnaires. While the data analysis technique used is to use Multiple Linear Regression Analysis using two statistical test methods, namely Simultaneous Test (Test f). Based on the results of research with statistical data analysis, the indicators in this study are valid and the variables are reliable. In the classical assumption test, it is proven that all indicators are normally distributed and there is a significant linear relationship between each independent variable and the dependent variable, for influence Segmentation, Targeting, and Positioning all have a positive direction and are not significant in their influence on the sales volume at Cafe Teras Empang in Parepare City.